(untitled) (Educational Dimension, 2023)
Objective: This study aims to develop a comprehensive methodology for integrating cloud-based learning tools into software engineering education for students in higher education institutions (HEIs). Research tasks: The research encompasses exploring the psychological and pedagogical aspects of software engineering education in HEIs, investigating the influence of cloud technologies on higher education, designing a robust model for implementing a methodological system that incorporates cloud-based learning tools, and conducting an experimental implementation of the proposed model. Research focus: The research focuses on the teaching and learning process of software engineering disciplines among students in HEIs, specifically emphasizing the utilization of cloud-based learning tools. Research methods: The research methodology involves analyzing relevant scholarly publications, dissertations, conference proceedings, and seminars, along with studying the experiences of educators through surveys and questionnaires. Additionally, the research incorporates practical experimentation with cloud-based learning tools. Research findings: The study highlights the crucial need to prioritize fundamental knowledge acquisition in software engineering education, which can be facilitated by the mobility features inherent in cloud-based learning tools. Furthermore, it reveals a significant correlation between emerging trends in information technology and the development of methodological teaching systems. The analysis underscores the transformative impact of cloud technologies on learning tools and other key components of the methodological teaching system. The research successfully implements an experimental model that integrates cloud-based learning tools into the methodological system. Conclusions and recommendations: The findings demonstrate that cloud technologies profoundly influence the technological aspects of the methodological system while simultaneously shaping the objectives and curriculum of IT professionals. The developed methodological system, which incorporates cloud technologies, plays a pivotal role in fostering the foundational education of IT professionals.